Forming Logical Thinking Through Mathematics For Primary Class Students - Ermamatova Maftuna; Akramova Lola O‘lmasovna (Genius Journals, 2024)
This article is written about improving students' knowledge, skills and abilities in solving logical problems in elementary mathematics classes.
Keywords: math; problem; practical